Natural versus Artificial Hormonal Cyclicity and Estrogen-Induced Hippocampal Cognitive Strategies in Coping with Stress and Pain - Belloum, Mohamed (Sciences de l'Homme et de la Société, 2013)
The aim of this paper is to shed some light on the influence of natural hormonal cyclicity (as opposed to artificial or manipulated hormonal cyclicities) on cognitive coping strategies.The paper approaches three contemporary interdependent issues or fields of enquiry : contraception, emotional intelligence & hippocampal cognitive strategies. The conclusions and findings, arrived at, point to the fact that cognitive strategies in coping with stress and pain, in women, depend essentially on a lunar-menstrual phase-locking and a natural cyclic activation of estrogen receptors in the hippocampus.      يهدف المقال إلي الكشف عن علاقة كل من هرمون الاستروجين و الدورة الشهرية الطبيعية لدى المرأة بتفعيل بعض الستراتيجيات المعرفية للتعامل مع الضغط و الألم، حيث تم التطرق إلي مخاطر حبوب منع الحمل، من جهة، و إضطرابات الدورة الهرمونية الطبيعية، من جهة أخري، على الصحة النفسية و عمليات التعلم على مستوى الدماغ العاطفي. الخلاصة التي تم التوصل إليها تتمثل في أن إستراتيجيات التعامل مع الظغوط و الألم عند الرأة تعتمد أساسا على علاقة ثلاثية بين دورة هرمون الأستروجين، الدورة القمرية ( الشهر القمري) و تنشيط مستقبلات الأستروجين على مستوى خلايا الحصين ( حصان البحر) بالدماغ العاطفي.